RANCANGAN AKSES PINTU MASUK DAN KELUAR PADA GEDUNG MPS (MAIN POWER STATION) DI BANDAR UDARA INTERNASIONAL SOEKARNO – HATTA - Muhamad Fiqri; Suse Lamtiar S; Ahmad Kosasih (Langit Biru: Jurnal Ilmiah Aviasi, 2019)
Entry and exit draft access of MPS (Main Power Station) is intended as an alternative to provide security and facilitate the work of technicians in airport services especially in Soekarno – Hatta International Airport. The problem now days is the person who is not licensed can get in and out easily in the MPS building and if the technicians carry goods because of difficult and the stuck of the door when opening or closing. This design consists of Microcontroller that used as RFID (Radio Frequency Identification) control or identity identifier and automatic door system. This design is expected to be used properly as expected and can help the technician in performing his works as one of the supporters of fluency and comfort at the Soekarno – Hatta International Airport.